Relationship Between Controlled and Uncontrolled Type 2 Diabetes Mellitus Against Ischemic Stroke - Linda Linda (Jurnal EduHealth, 2023)
Background: Stroke is a cerebrovascular disease that causes death and disability in the third world. In 2015, the World Health Organization (WHO) estimated that there are 20 million people with will die from a stroke. Ischemic Stroke is caused by a supply interruption of blood to the brain. The risk factor for ischemic Stroke is a non -modifiable factor risk factors such as age, race, gender, genetics, and modifiable risk factors in the form of a history of Transient Ischemic Attack or previous Stroke, hypertension, smoking, obesity, dyslipidemia, diabetes mellitus type2. Methods: An analytic observational study of 60 T2DM patients diagnosed with ischemic Stroke in Batang Hospital using medical record data then records the value of fasting blood sugar levels and Blood Sugar 2 Hours Post Prandial. The data was then analyzed using the chi-square test method with a mark of p<0.05. Results: There is a connection Which significant between Diabetes mellitus controlled And not controlled to stroke incident ischemic with mark p.s: 0.023 And mark OR (95%CI) = 4.71. Conclusion: The connection between Diabetes mellitus type 2 controlled And not controlled to incident strokes is ischemic significant.